NANO TREATMENT OF DECAYED CEMENT-LIME MORTARS FROM THE EDFENA ROYAL PALACE (ROSETTA, EGYPT) - Abubakr MOUSSA (Fayoum University, 2018)
This article focuses on the identification of the used building materials and their most common degradation factors at the royal palace of king Farouk at Edfena, Rosetta, Egypt; and then assessing the most appropriate nano-consolidants for the decayed lime-based mortars at the palace, to achieve the target of this study; building materials were studied by means of XRD, FTIR spectroscopy and light optical microscope; in order to find out if there are any chemical decomposition or any physical failure. Halite salt was detected in the building limestone; mortars’ composition varies between lime and white Portland cement, while the plaster in the palace walls is a mixture of white Portland cement and lime. Plaster in the marina is a mixture of lime, white Portland cement and anhydrite. Pigment material in the green terrazzo is a mix of malachite and greenalite; portlandite abreast with brucite were found in the plaster and mortar mixtures in addition to clay minerals. Nanolime, nanotitanium, nanokaolin, nanosilica and multi-walled carbon nanotubes were used as consolidants, experimental study made it clear that nanotitanium and MWCNTs are the most appropriate consolidants in the current case study.